Absence of cardiac impairment in patients after severe acute respiratory syndrome coronavirus type 2 infection: A long-term follow-up study - Janek Salatzki; Andreas Ochs; Lukas D. Weberling; Jannick Heins; Marc Zahlten; James G. Whayne; Christian Stehning; Evangelos Giannitsis; Claudia M. Denkinger; Uta Merle; Sebastian J. Buss; Henning Steen; et al. (Journal of Cardiovascular Magnetic Resonance)
Background: Concerns exist that long-term cardiac alterations occur after severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2) infection, particularly in patients who were hospitalized in the acute phase or who remain symptomatic. This study investigates potential long-term functional and morphological alterations after SARS-CoV-2 infection. Methods: The authors of this study investigated patients after SARS-CoV-2 infection by using a mobile 1.5T clinical magnetic resonance scanner for cardiac alterations. Cardiac function and dimensions were assessed using a highly efficient cardiac magnetic resonance protocol, which included cine sequences, global longitudinal and circumferential strain assessed by fast-Strain-ENCoded imaging, and T1 and T2 mapping. We assessed symptoms through a questionnaire. Patients were compared with a control group matched for age, gender, body mass index, and body surface area. Results: Median follow-up time was 395 (192-408) days. The final population included 183 participants (age 48.4 ± 14.3 years, 48.1% male (88/183)). During the acute phase of SARS-CoV-2 infection, 27 patients were hospital-admitted. Forty-two patients reported persistent symptoms (shortness of breath, chest pain, palpitations, or leg edema), and 63 reported impaired exercise tolerance. Left ventricular (LV) functional and morphological parameters were within the normal range. T1- and T2-relaxation times were also within the normal range, indicating that the presence of myocardial edema or fibrosis was unlikely. Persistently symptomatic patients showed a slightly reduced indexed LV stroke volume. Functional parameters remained normal in patients who were hospitalized for SARS-CoV-2, persistently symptomatic, or with ongoing impaired exercise tolerance. Conclusion: Irrespective of ongoing symptoms or severity of prior illness, patients who have recovered from SARS-CoV-2 infection demonstrate normal functional and morphological cardiac parameters. Long-term cardiac changes due to SARS-CoV-2 infection appear to be rare.